Students Mathematical Problem Solving Abilities With a Culturally Responsive Teaching Approach: Systematic Literature Review - Rohmad Nurwidi; Muchtadi Muchtadi; Hodiyanto Hodiyanto (FKIP - Universitas Riau, 2026)
The low mathematical problem-solving ability of Indonesian students is often attributed to learning designs that neglect students' cultural backgrounds, making the material feel abstract and less relevant. This study aims to synthesize research findings regarding the implementation of Culturally Responsive Teaching (CRT) and ethnomathematics in improving the mathematical problem-solving abilities and self-efficacy of Junior High School (SMP) students. This study employs a Systematic Literature Review (SLR) method using PRISMA 2020 guidelines, reviewing 28 selected articles from 1,248 publications between 2019-2024 across five reputable databases. The synthesis results indicate that integrating CRT with learning models such as Problem-Based Learning (PBL) and Realistic Mathematics Education (RME) consistently has a positive impact on critical and reflective thinking skills, as well as strengthening students' self-confidence through relevant cultural contexts. Although there are challenges related to teacher training and the lack of culture-based learning resources, it is concluded that the CRT approach is an effective, inclusive, and contextual pedagogical strategy to improve the quality of mathematics learning, which requires continuous training support for teachers.